Prevalence of Oral Maxillary and Mandibular Tori among Outpatients Attending Dental Collage in Basra Governorate Southern of Iraq (Medico Legal Update, 2021)
The objectives of the study is the assessment of torus palatinus (TP) prevalence as well as torus mandibularis (TM) among different gender and age groups. Seven hundred and fifty (750) out door patients (380 maleand 370 female) were tested for the tori presence or absence at dentistry collage in Basrah city betweenJanuary 2019 and June 2019. Sex, gender and location factors were evaluated. The prevalence rate of TPwas 4.73% for male and 5.13% for female, and the prevalence rate of TM was 2.36% for male and 3.24%for female. In females, TP prevalence was more compared to males. The TP incidence more commonly inmiddle aged persons, While the TM more commonly in older persons.